2017
DOI: 10.1097/md.0000000000007766
|View full text |Cite
|
Sign up to set email alerts
|

Serum HBeAg and HBV DNA levels are not always proportional and only high levels of HBeAg most likely correlate with high levels of HBV DNA

Abstract: This study aimed to investigate the correlation between quantitative hepatitis B e antigen (HBeAg) and hepatitis B virus (HBV) DNA levels, and to determine whether semiquantitative measurement of HBeAg can indicate the extent of HBV replication in HBeAg-positive subjects in the immune tolerant phase.A cross-sectional, community-based survey was carried out in 12 communities of 2 counties in Zhejiang Province, China. A panel of 788 HBeAg-positive subjects was divided into 4 groups according to HBV DNA level.Gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 23 publications
1
18
1
Order By: Relevance
“…To determine whether HBV DNA was linearly related to HBsAg and HBeAg, a regression analysis between HBsAg, HBeAg, and HBV DNA had been performed, respectively. The correlation coefficients between HBsAg and HBV DNA, HBeAg, and HBV DNA were 0.16 and 0.28 respectively, which was lower than the reported 0.69 and 0.74 …”
Section: Discussioncontrasting
confidence: 73%
“…To determine whether HBV DNA was linearly related to HBsAg and HBeAg, a regression analysis between HBsAg, HBeAg, and HBV DNA had been performed, respectively. The correlation coefficients between HBsAg and HBV DNA, HBeAg, and HBV DNA were 0.16 and 0.28 respectively, which was lower than the reported 0.69 and 0.74 …”
Section: Discussioncontrasting
confidence: 73%
“…Therefore, HBeAg has been regarded as an important indicator of disease severity; it also contributes to disease diagnosis and the formulation of treatment strategies. However, the results of the present and other studies have demonstrated that serum HBeAg patterns are not always positively associated with HBV DNA levels (23). To be more precise, several factors, including patients' demographic characteristics, should be considered in the treatment, prognostication and assessment of disease progression.…”
Section: Discussionmentioning
confidence: 53%
“…Hepatitis B e antigen (HBeAg) is a critical indicator to determine the severity of the disease and it is associated with the activity of viral replication and infectivity (22). In addition, HBeAg analysis is useful for predicting seroconversion and disease progression (23). However, how HBeAg expression influences HBV DNA levels, liver function and hepatic fibrosis remains elusive.…”
Section: Factors Associated With Disease Progression and Viral Replicmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, few studies have assessed the correlation between HBeAg and serum HBV DNA. A survey carried by Ping Chen, Qinfen Xie, et al[30] showed the highest levels serum HBV DNA ( > 10 7 copies/mL) with 768 S/CO of the HBeAg level, which could indicate the relation of HBV DNA level in IT phage. In the current study analyzed the whole course of CHB in clinic.…”
mentioning
confidence: 95%